A roadmap to enhancing community based participatory research strategies and collaborative efforts with populations impacted by commercial sexual exploitation. (May 2022) - Godoy, Sarah M.; Thelwell, Mikiko; Perris, Georgia E.; Freeman, Oree; Elander, Sara; Bath, Eraka P.
Highlights: Researchers should assess emotional readiness of communities with lived experience. Collaborators must recognize the value of lived experience. Honor holistic identities beyond prior histories of exploitation. Incentivize collaborators through fair remuneration and other means. Abstract: We integrated core community based participatory research (CBPR) principles in an intervention research study that aimed to address the sexual health needs of system-involved youth with histories of commercial sexual exploitation (CSE). Researchers, multidisciplinary stakeholders, and individuals with lived experience built upon each other's strengths and resources to adapt an evidenced-based reproductive health curriculum and develop an innovative sexual health intervention. This article presents key findings and recommendations that researchers can implement prior to, during, and after engaging individuals with lived experience and multidisciplinary stakeholders to support a prosperous bi-directional relationship. It is imperative that all collaborators recognize the value of lived experience and create a culture that encourages contributions beyond one's history of exploitation. Conducting an assessment to ensure individuals with lived experience feel mentally and emotionally prepared to participate may help reduce the potential for re-traumatization. Given the dearth of available health-related interventions for this population and strategies to guide collaboration, our findings may inform future efforts aimed at reducing health disparities, promoting equity, and improving sexual health outcomes amongst this population.